Ali kozača Strix uralensis gnezdi na Ljubljanskem barju? - Vrezec, Al (Društvo za opazovanje in proučevanje ptic Slovenije, 2015)
During the winter 1993/94 the author observed, in the so-called Kozlerjeva gošča forest reserve at Ljubljansko barje (Ljubljana Marshes), a pair of Ural Owls Strix uralensis macroura. From December to March, 8 records were made. The owls frequented the forest edge, and it was only once that the female was seen flying to the maize field nearby. Although the time of observor the assumption that the owl bred in the forest reserve, the author states three reasons which do not speak in favour of such possibility: 1) Utterly non-breeding disposition of the observed Ural Owls (winter vagrancy), 2) The forest reserve is too small to be a suitable breeding habitat for this bird, 3) Human disturbance. To the Ural Owl observed at Ljubljansko barje the authorattributes the status of a periodic visitor.